(untitled) (Kinesiology, 2017)
The purpose of the present study was to investigate the effects of feedback on the freestyle swimming learning and performance of novice swimmers. Sixty male (Mage=18.7, SD=1.82) first year students were randomly assigned into four groups: self-modeling, expert-modeling, verbal, and control group. The intervention program lasted for seven weeks. Participants were evaluated in 25m freestyle swimming, with a pool buoy between their legs and breathing every three hands through a pre-test, a post-test and a retention test. The result revealed that self-modeling group was the most effective, in comparison with the other types of feedback, in terms of improvement of the technique in novice swimmers. There were no differences between the groups in the speed performance of 25m freestyle swimming. Overall, the present study provides valuable evidence for the effects of self-modeling on performance in freestyle swimming, and encourages research to further explore such effects between different types of feedback in real training conditions. Key words: verbal feedback, visual feedback, expert-modeling, self-modeling, swimming